2006
DOI: 10.1111/j.1365-2958.2006.05459.x
|View full text |Cite
|
Sign up to set email alerts
|

The major surface‐metalloprotease of the parasitic protozoan, Leishmania, protects against antimicrobial peptide‐induced apoptotic killing

Abstract: SummaryHuman infection by the vector-borne protozoan Leishmania is responsible for substantial worldwide morbidity and mortality. The surface-metalloprotease (leishmanolysin) of Leishmania is a virulence factor which contributes to a variety of functions including evasion of complement-mediated parasite-killing and host intramacrophage survival. We tested the hypothesis that leishmanolysin serves to protect parasites from the cytolytic effects of various antimicrobial peptides (AMPs) which are important compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 59 publications
(85 reference statements)
9
101
0
2
Order By: Relevance
“…1). Moreover, the VIP derivatives showed lower EC 50 values than VIP for all of the bacteria strains assayed (Table 2). Interestingly, the VIP derivatives, but not VIP, were able to efficiently kill Gram-positive bacteria (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1). Moreover, the VIP derivatives showed lower EC 50 values than VIP for all of the bacteria strains assayed (Table 2). Interestingly, the VIP derivatives, but not VIP, were able to efficiently kill Gram-positive bacteria (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We calculated EC 50 , which represents the concentration of the peptide that reduces to 50% the viability of each bacteria and parasite strain, by using four-parameter logistic curve-fitting software (SigmaPlot).…”
Section: Microorganisms and Growth Conditions-streptococcus Mutans (Cmentioning
confidence: 99%
“…Leishmanolysin-deficient para- sites have been shown to have diminished virulence in mice, which has been attributed to their enhanced susceptibility to complement-mediated lysis (13,25). We hypothesize that multiple additional leishmanolysin-dependent events may account for these results, including the inability of these parasites to degrade FN and generate FNd for M deactivation and the ability of these parasites to degrade and inactivate host antimicrobial peptides (15). CPs may also contribute to these processes.…”
Section: Discussionmentioning
confidence: 93%
“…We tested both L. amazonensis promastigotes and amastigotes for this analysis and found that preincubation with antileishmanolysin antibody did not diminish the association of FN-FITC with either parasite form. Second, we compared both the wild type and the gp63 KO mutant of L. major lines (13,15) for their degree of FN-FITC binding (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…3,4,18 In addition, inhibitory enzymes present in bodily fluids and expressed extracellularly from pathogenic microorganisms will also decrease effective concentration levels of AMPs. [19][20][21][22] One challenge, therefore, is to develop methods that will increase the stability of cationic AMPs and protect them from inactivation without repressing their antimicrobial effect. In many applications in biochemical and biomedical engineering, protein stability and protection is maintained through the use of mineralization or polymerization reagents to encapsulate and retain protein activity (e.g., sol gels, epoxy resins, synthetic phospholipid vesicles, and polymer sponges).…”
Section: Introductionmentioning
confidence: 99%